INTEGRATED ENTERPRISE MANAGEMENT SYSTEM BASED ON THE ISO HIGH-LEVEL STRUCTURE - V. I. Shipulin; E. N. Mikheeva; N. D. Lupandina; T. A. Barsukovskaya (Современная наука и инновации, 2022)
The diversity of the requirements of the organization (the enterprise) the achievement of the business objectives can be successfully realized with the establishment of an integrated management system aimed at the effective implementation of legal requirements, ensure the satisfaction of consumers and stakeholders, sustainable development. The article considers the background to the establishment of integrated management systems of food industry enterprises on the basis of the implementation of the «high-level structure».